Film Recommendation Analysis with Sequential Pattern Discovery Algorithm Using Equivalence classes (SPADE) - Aisyah Amini Nur; Akbar Hidayatullah Harahap; Ihsan Muttaqin Bin Abdul Malik; Muhammad Irfan Nur Imam; Muhammad Thariq Sabiq Bilhaq; Angelyna Angelyna (UIN Sunan Gunung Djati Bandung, 2021)
Currently, the internet is the most essential thing in human life. So that there is a change in human needs, one of which is enjoying entertainment. With the internet, enjoying entertainment can be done anywhere and anytime, one of the entertainment is movies. With the internet, many service providers provide movie watching sites online. So that people become interested and use it a lot to watch movies online. With the increase in film fans, a film recommendation system is required to make a film recommendation pattern based on previous movie viewing. Therefore, this study aims to provide recommendations for viewing films using the pattern recognition method that often occurs. The technique used is sequence pattern mining using SPADE to find patterns from a group of data. SPADE's advantage is its speed in finding sequence frequencies that can be used as movie recommendation data from previous shows.